Decision Making assessed by the Iowa Gambling Task and Major Depressive Disorder A systematic review - Siqueira,Alaise Silva Santos de (2018)
Abstract Major Depressive Disorder (MDD) can occur in parallel with cognitive impairment. The search for a neuropsychological profile of depression has been pursued in the last two decades. However, scant research has been done on executive functions and decision-making ability (DM). Objective: To perform a systematic review of the evidence of DM performance evaluated using the Iowa Gambling Task (IGT) in adults with MDD. Methods: A systematic search according to the PRISMA statement was performed on MEDLINE for studies in English using the following keywords: ‘depression’, ‘depressive’, ‘depressive symptoms’ AND ‘decision making’ OR ‘game task’. Results: Five articles that met the inclusion and exclusion criteria were identified. Three reported significant differences between depressed and non-depressed individuals. The results indicated that young adults with MDD exhibited lower performance on all or almost all stages of the IGT. One study that evaluated DM in older adults with MDD showed that depressed non-apathetic participants failed to adopt any advantageous strategy and continued to make risky decisions during the task. Conclusion: Results suggest that performance on the DM task by young and old adults with MDD differed in comparison to non-depressed participants. Given the small number of articles, further studies should be performed.